Diagnostic Assessment of Skills Social Activities of Children in Early Childhood Education: Teacher Training Project in Centers (Centro "La Inmaculada" of Hortaleza) -First part- - Rosalía Aranda Redruello (Tendencias Pedagógicas, 2015)
Early Attention implies, in the First Stages of Education, the training of teachers, parents and educators who will take part in the child´s process of development. It also means the possibility of a positive influence in that development and in the improvement of the environment through all the educative actions with that target. This intervention in the process of learning will be defined by the enhancement and development of their physical, intellectual and social possibilities through systematic and sequenced programmes that include all the areas of the human development. At the same time, we will develop educative techniques whose target is the child and his/her family. To get this aim, we propose a project focusing on the teacher training in specific areas such as the teaching process, the methodology and action-research techniques in the centre so as it is useful both for teachers and students to develop social abilities. Social abilities are tightly related with the cognitive development and the learning the child acquires at school. Moreover, they are a necessary ingredient for the child to have a good socialization with his/ her mates and that is why we think it is necessary an attitude favouring the appearance of positive behaviours. Behaviour is clearly something neither parents nor teachers can ignore.